EARLY AND BETTER MATURITY IN CARP BROOD STOCK WITH CONROL OF ENVIRONMENT AND FEEDING - GHOSH, A.; ROY, P. K. (Journal of Indian Fisheries Association, 2015)
Availability of carp breeders in their prim state of maturity is a major constraint inhypophysation. Experiments conducted in a fish farm at Naihati, West Bengal, for twoconsecutive years, 1983-84 and 1984-85, clearly prove that by manipulation of environmentalparameters s~ch as metabolites, dissolved oxygen, running water conditions, as also of stockdensities and quality and quantity of feed, Cat/a cat/a, Hypophythalmichthys molitri'C, Labeorohita, Cirrhina mrigala and Ctenopharyngodon it/ella can be made to attain better maturityand SJ)awning stage much earlier than norntal i.e. even in summer months and the entirestock spawned during the period from March to September. Percentage of successful breeding,quantities of eggs realeased and fertilised in •·elation to the body ·weight of all the species,were also found to be more in comparison to the brood stock raised through the conventionalmethods.